의성 자두 대석조생, 후무사, 추희의 영양성분과 항산화 활성 비교 분석 - 엄정영(Jung-Young Eom); 김현진(Hyun-Jin Kim); 최상헌(Sang-Hun Choi); 서현주(Hyun-Ju Seo); 전익조(Ik-Jo Chun); 성지혜(Jeehye Sung); 임재환(Jae Hwan Lim); 권인숙(In-Sook Kwun); 조영은(Young-Eun Cho) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
본 연구는 동양계 자두 품종 중에서 의성 자두인 대석조생, 후무사, 추희 품종의 영양성분 및 항산화 활성을 평가하였다. 총 식이섬유는 대석조생> 후무사> 추희 순으로 대석조생이 가장 높았다. 칼슘 함량에서는 대석조생> 추희> 후무사 순으로 대석조생이 칼륨, 칼슘, 인의 함량이 모두 높은 것으로 나타났다. 총 폴리페놀 함량은 추희, 대석조생이 유의적으로 높았고 총 플라보노이드 함량은 대석조생이 유의적으로 가장 높았다. 항산화 활성은 대석조생> 후무사> 추희 순으로 대석조생이 가장 높았다. 따라서 동양계 자두인 의성 자두는 식이섬유 함량이 높고 열량이 낮으며, 높은 항산화 활성을 갖고 있어 다양한 건강 기능성 식품 소재로 활용도가 높을 것으로 사료된다. In this study, we investigated the chemical properties and antioxidant activities of Prunus salicina cultivars. We analyzed the nutritional ingredients, minerals, total polyphenols, total flavonoids, total fiber, and antioxidant activities of Prunus salicina Daeseok, Formosa, and Chuhui produced in Uiseong. There were no significant differences in the carbohydrate composition i.e., fructose, sucrose, and maltose between Prunus salicina Daeseok, Formosa, and Chuhui. Trans fat and cholesterol were not detected in any of the cultivars. The highest contents of P, K, and Ca were observed in the descending order of Prunus salicina Daeseok, Formosa, and Chuhui. In addition, the highest contents of total polyphenol and flavonoid were significantly detected in Prunus salicina Daeseok. Furthermore, the highest content of total fiber was observed in Prunus salicina Daeseok and Formosa. The highest antioxidant activities were observed in Prunus salicina Daeseok compared to Formosa and Chuhui. Taken together, these results suggest that Prunus salicina Daeseok produced in Uiseong could help develop antioxidant products. KCI Citation Count: 2